2020
DOI: 10.21203/rs.3.rs-136543/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher SARS-CoV-2 Seroprevalence in Workers with Lower Socioeconomic Status in Cape Town, South Africa.

Abstract: Background: South Africa has a high degree of inequality between population groups. The first wave of COVID-19 may have affected people in lower socioeconomic groups worse than the affluent. The SARS-CoV-2 seroprevalence and the specificity of anti-SARS-CoV-2 antibody tests in South Africa is not known. Methods: We tested 405 volunteers representing all socioeconomic strata from the workforce of a popular shopping and tourist complex in central Cape Town with the Abbott SARS-CoV-2 IgG assay. We assessed the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
3
19
1
Order By: Relevance
“…These significant differences most likely can be explained by historically based socio-economic factors which hinder the implementation of COVID-19 preventative measures at a community level. Previous seroprevalence estimates from South Africa, specifically the Western Cape province (not included in our analysis), earlier in the epidemic found: 1) a very high prevalence (30-40 percent) among pregnant women attending state sector antenatal care, and people living with HIV presenting for routine viral load assessment (7); and 2) higher prevalence among workers with lower socioeconomic status (8). A review of population-based seroprevalence studies in Europe, America and Asia reported a seroprevalence range of <0.1% to more than 20% in the different regions (2).…”
Section: Discussionmentioning
confidence: 86%
“…These significant differences most likely can be explained by historically based socio-economic factors which hinder the implementation of COVID-19 preventative measures at a community level. Previous seroprevalence estimates from South Africa, specifically the Western Cape province (not included in our analysis), earlier in the epidemic found: 1) a very high prevalence (30-40 percent) among pregnant women attending state sector antenatal care, and people living with HIV presenting for routine viral load assessment (7); and 2) higher prevalence among workers with lower socioeconomic status (8). A review of population-based seroprevalence studies in Europe, America and Asia reported a seroprevalence range of <0.1% to more than 20% in the different regions (2).…”
Section: Discussionmentioning
confidence: 86%
“…(2021) in RSA found that seroprevalence was higher in participants with hypertension (15 [15.6%]) than diabetes (10 [10.4%]). 21 , 42 Alemu et al. (2020), in Ethiopia found that prevalence was higher in married 13 (9.8%), compared to single 9 (6.8%), or divorced/widowed 1 (2.8%).…”
Section: Resultsmentioning
confidence: 97%
“…Individuals in low-income communities with crowded housing, a reliance on public transport and higher numbers of essential workers are less able to implement and maintain social distancing and non-pharmaceutical interventions (NPIs) 7 . And they therefore are more likely to get infected with COVID-19, as demonstrated in several South African seroprevalence studies [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…While the authors note the limitations of using race as a proxy for socio-economic status, their study highlights the limitations of NPIs in communities with economic deprivation and high population density, or conversely how effective NPIs can be when they are feasible 15 . A study on shopping mall workers in Cape Town found a high seroprevalence was associated with informal housing, living in a sub-district with a low-income per household and having a low-earning occupation 16 .…”
Section: Discussionmentioning
confidence: 99%